Implementing a Standardized Prehospital Medical Record in Emergency Nursing Practice: A Qualitative Study in an Urban EMS Service - Deswita Aridhya Anjali; Asti Melani Astari; Rinik Eko Kapti; Suryanto Suryanto (Media of Health Research, 2026)
Documentation is a fundamental component of professional nursing practice, supporting clinical accountability, continuity of care, and patient safety. In prehospital emergency settings, documentation is often challenged by time constraints, dynamic environments, and limited standardization. This study explored ambulance nurses' experiences following the implementation of a standardized prehospital medical record form in a municipal emergency medical service in Indonesia. A qualitative descriptive design was conducted at a Public Safety Center (PSC 119) in an urban setting. Four active ambulance nurses participated in a two-week implementation of the standardized form. Data were collected through a focus group discussion and analyzed using inductive content analysis, with independent coding and an audit trail to enhance trustworthiness. Six themes emerged: perceived additional workload, clinical benefits, operational barriers, administrative and communication barriers, professional challenges in documenting clinical aspects, and expectations for system optimization. Although initially viewed as increasing the workload, the standardized form was perceived as improving systematic assessment and completeness of documentation. Time pressure, operational demands, and uncertainty regarding diagnostic authority affected nurses' confidence and documentation practices. Overall, standardized prehospital documentation offers important professional and patient safety benefits but requires workflow-sensitive implementation, organizational support, and strengthened clinical confidence within nurses' scope of practice to promote sustainable adoption.